Using Social Media to Assess Expressions of Gratitude to God: Issues for Consideration - Tay, Louis ca. 20./21. Jh. (Religions, 2022)
With the proliferation of technology-based communication, public expressions of gratitude to God on social media have become more pervasive. At the same time, data science approaches are increasingly being applied to social media language data to assess positive human attributes. We elucidate critical considerations in assessing public expressions of gratitude to God, including language variability and comparability, degree of authenticity, machine learning language analysis, and aggregation approaches that could affect assessment accuracy.